Diversity of Aerial Insects and their Status in Nagara Sweet Potato (Ipomea batatas L.) Crops in Lebak Swamp - M. Renaldi; Akhmad Gazali; Rila Rahma Apriani (DIVERSITAS HAYATI, 2025)
South Kalimantan possesses the potential for extensive wetland swamps that have not been fully utilized optimally for agricultural purposes. One particular commodity that demonstrates adaptability to the unique characteristics of the swamp environment is the Nagara sweet potato (Ipomoea batatas L.). The Nagara sweet potato plantation ecosystem is also a habitat for various types of aerial insects that play an important role in ecosystem balance, both as pests, natural enemies, and bioindicators. The objective of this study is to ascertain the diversity and status of aerial insects in Nagara sweet potato plantations on Lebak swamp land. The research was conducted from May to July of 2024 in Daha Selatan District, Hulu Sungai Selatan Regency. The research method employed was a descriptive exploratory approach, leveraging a purposive sampling technique. The collection of samples was executed through the utilization of sweep nets and yellow traps, followed by identification utilizing an insect determination key book. The results of the study indicated the presence of 12 species of aerial insects, classified into six orders and nine families, with specific details regarding their status. This included two pest species, six natural enemy species, and four bioindicator species. The Shannon diversity index (H') of 0.99 is low, the evenness index (E) of 0.895 is high, the species richness index (R) of 5.176 is high, and the dominance index (D) of 0.099 is low. The high presence of natural enemies suggests that the Nagara sweet potato plantation ecosystem is relatively stable and possesses the capacity for natural pest control. This finding can serve as a foundation for the development of a sustainable agricultural system on Lebak swamp.